Comparison of the characteristics and oxidation kinetic parameters of flaxseed (Linum usitatissimum L.) oil products with different refining degree. Issue 10 (17th July 2020) - Zhang, Youfeng; Li, Tiannan; Xu, Ziye; Liu, Ruijie; Zhang, Hui; Wang, Xingguo; Huang, Jianhua; Jin, Qingzhe
Abstract: Flaxseed oil is rich in polyunsaturated fatty acid, which is prone to oxidation. Physicochemical properties, bioactive minor components, and oxidation kinetic parameters of flaxseed oil products with different refining degree (filtration, degumming, and full refining) were investigated. The fully refined flaxseed oil has the lowest acid, peroxide, and p ‐anisidine values, which also showed the lowest contents of tocopherol, phytosterol, and polyphenol. The oxidation stability indexes of samples were 23.67–30.79, 10.97–12.81, 4.91–5.36, and 2.47–2.67 hr at 70, 80, 90, and 100°C, respectively. The activation energies ( Ea ), Q10 number, activation enthalpy (Δ H ), and activation entropy (Δ S ) values were 79.81–88.67 kJ/mol, 2.11–2.29, 76.83–85.70 kJ/mol, and from −179.61 to −176.70 J/mol K, respectively. Results indicated that remarkable loss of endogenous antioxidants may be the cause for the relatively weaker oxidation stability in completely refined flaxseed oil. This investigation provides basic data and theoretical support for the moderate refining of flaxseed oil. Practical applications: Flaxseed oil is rich in polyunsaturated fatty acid, the oxidation stability of flaxseed oil products should draw more attention. This investigation contributes to a better understanding of the characteristics and oxidation kinetics parameters of flaxseed oil products from different steps of refining processes. In addition, this research provides basic data and theoretical support for the moderate refining of flaxseed oil. Moreover, the results of the oxidation kinetic of flaxseed oil can be used to predict the process of oxidation under various conditions.